QUASI-ANALYTICAL METHOD FOR IMAGES CONSTRUCTION FROM GRAVITATIONAL LENSES - Kotvytskiy, A. T.; Bronza, S. D. (Одеські астрономічні публікації, 2016)
One of the main problems in the study of system of equations of the gravitational lens, is the computation of coordinates from the known position of the source. In the process of computing finds the solution of equations with two unknowns. The problem is that, in general, there is no analytical method that can find all of the roots (lens) of system over the field of real numbers. In this connection, use numerical methods like the method of tracing. For the N-point gravitational lenses we have a system of polynomial equations. The methods of algebraic geometry, we transform the system to another system, which splits into two equations. Each equation of the transformed system is a polynomial in one variable. Finding the roots of these equations is the standard computing task.